Homopropargyl alcohol 1,1-diphenylbut-3-yn-1-ol - Umaña, Christian A. (2018)
The asymmetric unit of the title compound, C16H14O, contains one molecule with a central carbon atom having a distorted tetrahedral geometry made of a propargylic fragment, a hydroxy group and two aromatic rings. Directional interactions such as unusual O—Hπ contacts are observed between the molecules in the crystal.